Reading Anxiety, Reading Self-Efficacy, and Reading Competency in The Senior High School - Ni Nengah Resti Marhaeni; Dewa Komang Tantra; I Putu Ngurah Wage Myartawan (Language and Education Journal Undiksha, 2020)
This study aimed at describing and relating the students’ reading anxiety, reading self-efficacy to their reading competency in SMAN 3 Singaraja. There are three research questions in this study, namely: (1) How are the students’ reading anxiety, reading self-efficacy, and their reading competency? (2) are there pair-wise relationships of students’ reading anxiety, reading self-efficacy, and reading competency? (3) Is there significant multiple correlation of the predictor and criterion variables? The three instruments were used to collect the data; reading anxiety scale, reading self-efficacy scale, and objective reading competency test. The obtained data were analyzed in two phases namely, descriptively and inferentially. The findings show that: (1) the students’ reading anxiety on higher-order-items is high, while reading self-efficacy and reading competency are low; (2) the negative correlations between reading anxiety, self-efficacy and competency; positive correlation between self-efficacy and competency, (3) negative multiple correlation between reading anxiety and self-efficacy to their competency.